Is there Room for Ethics within Bioinformatics Education? - Taneri, Bahar (Mary Ann Liebert, Inc, 2011)
When bioinformatics education is considered, several issues are addressed. At the undergraduate level, the main issue revolves around conveying information from two main and different fields: biology and computer science. At the graduate level, the main issue is bridging the gap between biology students and computer science students. However, there is an educational component that is rarely addressed within the context of bioinformatics education: the ethics component. Here, a different perspective is provided on bioinformatics education, and the current status of ethics is analyzed within the existing bioinformatics programs. Analysis of the existing undergraduate and graduate programs, in both Europe and the United States, reveals the minimal attention given to ethics within bioinformatics education. Given that bioinformaticians speedily and effectively shape the biomedical sciences and hence their implications for society, here redesigning of the bioinformatics curricula is suggested in order to integrate the necessary ethics education. Unique ethical problems awaiting bioinformaticians and bioinformatics ethics as a separate field of study are discussed. In addition, a template for an Ethics in Bioinformatics'' course is provided.
2nd Meeting on Bioinformatics Education, Res in Computational Molecular Biology (RECOMB-BE) -- MAY 22-23, 2010 -- San Diego, CA
Keywords: bioethics; bioinformatics; curricula; education; ethics